Participatory Design Research and Educational Justice: Studying Learning and Relations Within Social Change Making - Bang, Megan; Vossoughi, Shirin (Cognition and instruction, 2016)
Cognition and Instruction Participatory Design Research and Educational Justice: Studying Learning and Relations Within Social Change Making